Respostas
respondido por:
3
Resposta:
Resposta:
\begin{gathered}1 ^{2} - 2 \times 2 + 3 = 1 - 4 + 3 = 0 \\ 12 ^{2} - 2 \times 2 + 3 = 144 - 4 + 3 = 143 \\ 3 ^{2} - 2 \times ( - 2) + 1 = 9 + 4 + 1 = 14 \\ {13}^{2} - 2 \times 4 - 2 = 169 - 8 - 2 = 159\end{gathered}12−2×2+3=1−4+3=0122−2×2+3=144−4+3=14332−2×(−2)+1=9+4+1=14132−2×4−2=169−8−2=159
Explicação passo-a-passo:
espero ter ajudado <>
Perguntas similares
4 anos atrás
4 anos atrás
4 anos atrás
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás